PENGARUH PERLAKUAN AWAL DAUN/RANTING TANAMAN GAMBIR (UNCARIA GAMBIR ROXB) TERHADAP KADAR TANNIN EKSTRAK YANG DlHASILKAN DAN KEMAMPUAN PENYAMAKANNYA PADA KULIT KAMBING - Deni Novia (State Islamic University of Sultan Syarif Kasim Riau, 2009)
Target of this research is to know influence of treatment early leaf/stick of gambir to rate of tannin yielded extract and ability tanni:t1.g at leather goat. This research use mean analysis calculate average by 3 treatment and two restating that is A : leaf/stick of gambir fresh; B : materials heated above fire until w.ilting; C : materials soaked insalt condensation 2.25 %, 10 day, boiled 1000c, 5 minute. Perception of extract of gambir done to rate of tannin. Leather result tanning with gambir analysed by water contents, oil contents, dissolve. rate in water, dusty rate do not be dissolve, raw husk rate, tanner and degree of check. Result of research of leaf/stick of gambir heated by fire until w.ilting which eetracted have tannin 27.48%and degree ofcheck leather 151.51 %is the best totan goaL